Business Development case and Diversification Strategy for Silver Atena in the UK Automotive sector. - Sharma, Mrinal (2011)
This report explores a new market - UK automotive safety critical software services - for the company Silver Atena. Silver Atena has successfully established business in the safety critical area in Aerospace, Rail, Gas Turbines and Defence domains, providing end to end solution from software to hardware to high engineering. The aim of the report is to assess the new market, new competitors, and potential clients for Silver Atena and evaluate whether Silver Atena has the right internal capabilities to serve this market, cater to the clients and compete with the competitors. Additionally the report also provides a guide to Silver Atena where it can monitor the industry activities and potential business development area. Finally the report provides a customer value proposition for safety critical software services from Silver Atena. The report also refers to the relevant literature review in all the above areas. The report is broadly structured as follows: • Literature review of the relevant business areas required in this study • Analysis of the UK automotive safety critical software services market • Evaluation of the internal capabilities of Silver Atena • Identification and analysis of potential competitors and clients • Guide to monitor industry activities and business development areas • Customer value proposition of Silver Atena for safety critical software services